How long does carbon stay in a near-pristine central Amazon forest?: An empirical estimate with radiocarbon - Chanca, Ingrid; Levin, Ingeborg; Trumbore, Susan; Macario, Kita; Lavric, Jost Valentin; Quesada, Carlos Alberto; Carioca de Araújo, Alessandro; Quaresma Dias Júnior, Cléo; van Asperen, Hella; Hammer, Samuel; Sierra, Carlos (Biogeosciences, 2025)
Amazon forests play a significant role in the global C cycle by assimilating large amounts of CO2 through photosynthesis and by storing C largely as biomass and soil organic matter. To evaluate the net budget of C in the Amazon, we must also consider the amplitude and timing of losses of C back to the atmosphere through respiration and biomass burning. One useful timescale metric that integrates such information in terrestrial ecosystems is the transit time of C, defined as the time elapsed between C entering and leaving the ecosystem; the transit time is equivalent to the age of C exiting the ecosystem, which occurs mostly through respiration. We estimated the mean transit time of C for a central Amazon forest based on the C age during ecosystem respiration (ER), taking advantage of the large variations in CO2 in the atmosphere below the forest canopy to estimate the radiocarbon signature of mean ER (Δ14CER) using Keeling and Miller-Tans mixing models. We collected air samples to evaluate changes in the isotopic signature of the main ER sources by estimating the δ13CER. We collected air samples in vertical profiles in October 2019 and December 2021 at the Amazon Tall Tower Observatory (ATTO) in the central Amazon. Air samples were collected in a diel cycle from two heights below the canopy (4 and 24 m above ground level (a.g.l.)). Afternoon above-canopy samples (79 and 321 m a.g.l.) were collected as the background. For the campaign of October 2019, the mean Δ14CER ranged from 24 ‰ to 41 ‰ with both Keeling and Miller-Tans methods. In December 2021, mean Δ14CER ranged from 53 ‰ to 102 ‰. The δ13CER showed a smaller variation, being −27.8 ‰ ± 0.3 ‰ in October 2019 and −29.0 ‰ ± 0.5 ‰ in December 2021. The Δ14CER estimates were compared with the record of atmospheric radiocarbon from the bomb period, providing estimates of mean transit time of 6 ± 2 years for 2019 and 18 ± 4 years for 2021. In contrast to steady-state carbon balance models that predict constant mean transit times, these results suggest an important level of variation in mean transit times. We discuss these results in the context of previous model-based estimates of mean transit time for tropical forests and the Amazon region. In addition, we discuss previous studies that indicate that approximately 70 % of assimilated carbon is respired as autotrophic respiration in the central Amazon. Our results suggest that newly fixed carbon in this terra firme tropical forest is respired within 1 to 2 decades, implying that only a fraction of assimilated C can act as a sink for decades or longer.